IMPLEMENTASI KEBIJAKAN PENGELOLAAN PELAYANAN INFORMASI PUBLIK MELALUI WEBSITE PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI (PPID) DI KABUPATEN PURWOREJO - Ambar Sukmawati; Satria Aji Imawan (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Public information services through the PPID website of Purworejo Regency have not been utilized optimally despite the availability of supporting regulations and infrastructure. This study aims to describe and analyze the implementation of public information service management policy through the PPID website based on Purworejo Regent Regulation Number 24 of 2017, particularly Article 5 paragraph (2) and Article 8 letter (d), as well as to identify its driving and inhibiting factors using George C. Edwards III's policy implementation theory. This study employs a descriptive qualitative method with data collection through in-depth interviews, observation, and documentation studies, analyzed through data condentation, data presentation, and conclusion drawing. The results indicate that policy implementation has progressed gradually but has not been fully optimal. The availability of information systems, storage and documentation, as well as the provision of information to the public have run optimally, however, website accessibility and the reach of services to the community have not been optimal. Driving factors stem from adequate technical infrastructure, openly accessible SOPs, structured internal communication. Meanwhile, inhibiting factors include dual workloads of personnel, gaps in OPD operator understanding of public information disclosure substance, the absence of knowledge transfer mechanisms during personnel turnover, lack of dedicated budget allocation, and minimal specific outreach to the community.